Prevention and management of hearing loss in syndromic craniosynostosis: A case series. (June 2016) - Biamino, Elisa; Canale, Andrea; Lacilla, Michelangelo; Marinosci, Annalisa; Dagna, Federico; Genitori, Lorenzo; Peretta, Paola; Silengo, Margherita; Albera, Roberto; Ferrero, Giovanni Battista
Abstract: Objective: To assess the audiological profile in a cohort of children affected by syndromic craniosynostosis. Methods: Eleven children with Apert syndrome ( n  = 4), Saethre-Chotzen syndrome ( n  = 3), Muenke syndrome ( n  = 2), Crouzon syndrome ( n  = 1) and Pfeiffer syndrome type 1 ( n  = 1) were submitted to a complete audiologic evaluation including otoscopy, pure-tone audiometry, tympanometry and acoustic reflex testing, ABR, otoacustic emissions, temporal bone High Resolution CT (HRCT) scan. The main outcome measures were prevalence, type and severity of hearing loss, prevalence of chronic otitis media, correlation with the time of first surgical correction. Results: Seven of 11 patients (64%) presented hearing loss (HL), conductive in 3/7 patients (43%) and mixed in 4/7 (57%). No patients showed a purely sensorineural HL. All hearing impaired patients displayed middle ear disorders: the patients with conductive HL had otitis media with effusion (OME) and 3/4 patients with mixed HL showed tympanic alterations or cholesteatoma. A bilateral vestibular aqueduct enlargement was detected by HRCT scan in one normal hearing patient. The ABRs resulted normal in all cases. Conclusion: Our study confirms the high prevalence of otologic diseases in such patients. In contrast with previous studies, middle ear disorders were responsible for the hearing impairment also in patients with mixed HL due to secondary inner ear damage. These findings restate the necessity of a close audiologic follow-up. We did not detect the specific ABR abnormalities previously reported, possibly because of an early correction of the cranial vault malformations.